2022
DOI: 10.1111/nph.18443
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics and metabolomics reveal specialized metabolite drought stress responses in switchgrass (Panicum virgatum)

Abstract: Switchgrass (Panicum virgatum) is a bioenergy model crop valued for its energy efficiency and drought tolerance. The related monocot species rice (Oryza sativa) and maize (Zea mays) deploy species-specific, specialized metabolites as core stress defenses. By contrast, specialized chemical defenses in switchgrass are largely unknown.To investigate specialized metabolic drought responses in switchgrass, we integrated tissuespecific transcriptome and metabolite analyses of the genotypes Alamo and Cave-in-Rock tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 60 publications
2
25
1
Order By: Relevance
“…We purified and elucidated the structure for a novel abietane type diterpenoid -Di287 -from switchgrass roots. In contrast to the previously identified Panicoloid diterpenoids (Di301 and Di317, Tiedge et al, 2022), the NMR evidence indicated lack of a furan moiety in the diterpene scaffold of Di287 (Fig S 4 -12). We then explored SAR of three different types of switchgrass diterpenes -Di301, Di317 and Di287 -with and without a furan moiety.…”
Section: B -D and Fig S2)contrasting
confidence: 91%
See 4 more Smart Citations
“…We purified and elucidated the structure for a novel abietane type diterpenoid -Di287 -from switchgrass roots. In contrast to the previously identified Panicoloid diterpenoids (Di301 and Di317, Tiedge et al, 2022), the NMR evidence indicated lack of a furan moiety in the diterpene scaffold of Di287 (Fig S 4 -12). We then explored SAR of three different types of switchgrass diterpenes -Di301, Di317 and Di287 -with and without a furan moiety.…”
Section: B -D and Fig S2)contrasting
confidence: 91%
“…(A) The structures of HPLC purified switchgrass saponins and diterpenoids used in the bioassays. The structures of the saponins D415-SCG, D415, D431 and D457, and the diterpenoids, Di301 and Di317, were previously elucidated by LC-MS/MS and NMR (Li et al, 2022; Tiedge et al, 2022). NMR data supporting the structure of diterpenoid Di287 can be accessed in the supplementary files ( Fig S 4 – 12, Table S7) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations